A genetic linkage map of the rat derived from recombinant inbred strains. - Pravenec, M; Gauguier, D; Schott, J; Buard, J; Kren, V; Bílá, V; Szpirer, C; Szpirer, J; Wang, J; Huang, H; St Lezin, E; Spence, M; et al. (1996)
We have constructed a genetic linkage map in the rat by analyzing the strain distribution patterns of 500 genetic markers in a large set of recombinant inbred strains derived from the spontaneously hypertensive rat and the Brown-Norway rat (HXB and BXH recombinant inbred strains). 454 of the markers could be assigned to specific chromosomes, and the amount of genome covered by the mapped markers was estimated to be 1151 centimorgans. By including a variety of morphologic, biochemical, immunogenetic, and molecular markers, the current map integrates and extends existing linkage data and should facilitate rat gene mapping and genetic studies of hypertension and other complex phenotypes of interest in the HXB and BXH recombinant inbred strains.